Tindakan Pencegahan Stunting Pada Ibu Hamil Melalui Sosialisasi Di Desa Muara Takus - Merri Silvia Basri; Rayyan Fahreza; Febri Ardiansyah; Vanessa Riszkika; Nabila Rafa Kalila; Gracia Fenita Harianja; Nur Latiffahni; Elfahruzi Gustyalfidha; Indah Sari Syafitri; Melda Mauliza; Ariel Shelley Janete Pardosi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Stunting is a public health problem that has a serious impact on child growth and development. Pregnant women play an important role in preventing stunting through adequate nutritional intake during pregnancy. One of the efforts made to prevent stunting is through socialization activities. From the results of measurement validation in XIII Koto Kampar Sub-district, Muara Takus Village, the target number of toddlers through Electronic Recording and Reporting of Community-Based Nutrition (e-PPGBM) is 204 people. Where the number of toddlers who experience stunting has decreased, from February as many as 15 people to September as many as 4 people.